Coronavirus antibody positive tests and continued use of personal protective equipment throughout the pandemic. Issue 8 (October 2020) - Herron, J.B.T.; Dennis, J.; Brennan, P.A.
Abstract: The COVID-19 pandemic has thrust not only a novel virus onto the world, but new challenges resulting in novel approaches. Governments have reduced regulation in order to facilitate timely advances to combat the disease. Antibody testing has rapidly been deployed but it is creating challenges for staff and patients. Mask use has come to the forefront and human factor (HF) strategies must be examined to reduce risk associated with lack of engagement from both healthcare staff and patients. In this we explore these issues and suggest some solutions.